Dynamic Access Control for Pervasive Grid Applications - Naqvi, Syed; Riguidel, Michel (Computational Intelligence and Security, 2005)
The current grid security research efforts focus on static scenarios where access depends on the identity of the subject. They do not address access control issues for pervasive grid applications where the access privileges of a subject not only depend on their identity but also on their current context (i.e. current time, location, system resources, network state, etc). Our approach complements current authorization mechanisms by dynamically granting permission to users based on their current context. The underlying dynamic and context aware access control model extends the classic role based access control, while retaining its advantages (i.e. ability to define and manage complex security policies). The major strength of our proposed model is its ability to make access control decision dynamically according to the context information. Its dynamic property is particularly useful for pervasive grid applications.